A citation analysis of faculty publications in Mapùa University with implications on the library collection development - Bautista, Jannice F.; Cabbab, Johann Frederick A.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines, 2017)
The main purpose of this study was to identify the capabilities of the Mapùa Library in supporting the research needs of its faculty members. The study sought to identify the types of resources utilized, preferred materials, and availability of such in the libraries of the Mapúa Universit
The study analyzed 4,738 citations from 229 research outputs of the Mapúa University faculty members searchable through Scopus. Research list and citations were exported from Scopus as .csv file and organized in an Excel database. All gathered citations were searched through EBSCO Discovery Service (EDS) and other database subscriptions of the Libra
Journal articles were the most cited type of material. Majority of the cited materials were published from 2001 to 2016, which shows that publications published recently were mostly consulted. Among the cited materials of faculty researchers, 32.58% are available in the Mapúa Library, 20.70% are from open sources, and 46.71% are not available from any of the collections of the Libr
Based on the results, recommendations for an updated collection development policy and suggested database subscriptions were m
Special Problem
Keywords: Bibliographical citations; Research -- Evaluation